Mental health disorder symptom prevalence and rates of help-seeking among University-Enrolled, emerging adults. Issue 1 (2nd January 2023) - Williams, Kofoworola D. A.; Adkins, Amy; Kuo, Sally I.; LaRose, Jessica G.; Utsey, Shawn O.; Guidry, Jeanine P. D.; ,; Dick, Danielle; Carlyle, Kellie E.
Abstract: Objective. Examine mental health symptom prevalence and rates of campus services utilization among Black male, White male and Black female college students. Participants. 2500 students from an ongoing, student survey at a public university; launched in 2011. Methods. Measures included data for anxiety and depressive symptoms and utilization of campus health services (counseling center, health services, etc.). Descriptive analyses determined prevalence and utilization rates. Mann Whitney U tests compared prevalence. Chi-squared tests compared utilization rates. Results. Anxiety prevalence: greater than 60% of students from each ethnic group reported symptoms; reporting rates decreased significantly for Black men (49.6%); p < 0.001. Depression prevalence: greater than 80% reported symptoms; there were significant differences in reporting between Black men and Black women (72.7% vs. 87.1%, p < 0.001). Utilization: Black men utilized counseling services less than White men (20.4% vs. 37.8%, p = 0.024). Conclusion. Black men report depressive and anxiety symptoms but underutilize campus health resources.